Proteomic Investigation Uncovers Potential Targets and Target Sites of Pneumococcal Serine-Threonine Kinase StkP and Phosphatase PhpP - Hirschfeld, Claudia; Gómez-Mejia, Alejandro; Bartel, Jürgen; Hentschker, Christian; Rohde, Manfred; Maaß, Sandra; Hammerschmidt, Sven; Becher, Dörte (Frontiers in Microbiology, 2020)
Like eukaryotes, different bacterial species express one or more Ser/Thr kinases and phosphatases that operate in various signaling networks by catalyzing phosphorylation and dephosphorylation of proteins that can immediately regulate biochemical pathways by altering protein function. The human pathogen Streptococcus pneumoniae encodes a single Ser/Thr kinase-phosphatase couple known as StkP-PhpP, which has shown to be crucial in the regulation of cell wall synthesis and cell division. In this study, we applied proteomics to further understand the physiological role of pneumococcal PhpP and StkP with an emphasis on phosphorylation events on Ser and Thr residues. Therefore, the proteome of the non-encapsulated D39 strain (WT), a kinase (ΔstkP) and phosphatase mutant (ΔphpP) were compared in a mass spectrometry based label-free quantification experiment. Results show that a loss of function of PhpP causes an increased abundance of proteins in the phosphate uptake system Pst. Quantitative proteomic data demonstrated an effect of StkP and PhpP on the two-component systems ComDE, LiaRS, CiaRH and VicRK. To obtain further information on the function, targets and target sites of PhpP and StkP we combined the advantages of phosphopeptide enrichment using titanium dioxide and spectral library based data evaluation for sensitive detection of changes in the phosphoproteome of the wild type and the mutant strains. According to the role of StkP in cell division we identified several proteins involved in cell wall synthesis and cell division that are apparently phosphorylated by StkP. Unlike StkP, the physiological function of the co-expressed PhpP is poorly understood. For the first time we were able to provide a list of previously unknown putative targets of PhpP. Under these new putative targets of PhpP are, among others, five proteins with direct involvement in cell division (DivIVA, GpsB) and peptidoglycan biosynthesis (MltG, MreC, MacP).